Pengaruh Latihan Afirmasi Positif terhadap Self Awareness pada Narapidana di Rumah Tahanan Klas IIB Majene - Aprilah Adelia; Fredy Akbar K; Nurul Aeni; Imran Yaman; Nur Aisyah (Yayasan Mandar Indonesia, 2026)
Every prisoner experiences psychological, social, and environmental pressures that may trigger low self-awareness. If not properly addressed, the decline in self-awareness can potentially lead to negative impacts, both intrapersonally and interpersonally. Positive affirmation is one of the self-hypnosis techniques proven to be effective in producing a high level of relaxation, thereby strengthening self-awareness. This study aimed to determine the effect of positive affirmation exercises on self-awareness among prisoners. The study employed a pre-experimental design with a one-group pretest–posttest approach. Sampling was conducted using a purposive sampling method, and 15 prisoners were selected through random selection. The level of self-awareness was measured using the Self Awareness Questionnaire-20 (SAQ-20) before and after the positive affirmation exercises. Data analysis with the Wilcoxon signed-rank test showed a p-value of 0.001 (p < 0.05), indicating a statistically significant increase in self-awareness after the intervention. The findings demonstrate that positive affirmation exercises are effective in enhancing self-awareness among prisoners. The implications of this study support the use of positive affirmation exercises as a simple and relevant psychological support intervention for prisoners, which may contribute to improving self-awareness both within correctional facilities and in preparation for social reintegration.